2018
DOI: 10.1002/ecy.2463
|View full text |Cite
|
Sign up to set email alerts
|

Local adaptation reduces the metabolic cost of environmental warming

Abstract: Metabolism shapes the ecosystem role of organisms by dictating their energy demand and nutrient recycling potential. Metabolic theory (MTE) predicts consumer metabolic and recycling rates will rise with warming, especially if body size declines, but it ignores potential for adaptation. We measured metabolic and nutrient excretion rates of individuals from populations of a globally invasive fish that colonized sites spanning a wide temperature range (19-37°C) on two continents within the last 100 yr. Fish body … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
61
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(79 citation statements)
references
References 57 publications
(109 reference statements)
6
61
1
Order By: Relevance
“…Individuals would reduce their metabolic thermal sensitivity to mitigate the increase in energy expenditure with warming, leading to lower activation energy values than the predicted 0.65 eV. Consistent with this hypothesis, Moffett et al (2018) reported that populations from warmer habitats have a lower thermal sensitivity than populations from cooler habitats.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…Individuals would reduce their metabolic thermal sensitivity to mitigate the increase in energy expenditure with warming, leading to lower activation energy values than the predicted 0.65 eV. Consistent with this hypothesis, Moffett et al (2018) reported that populations from warmer habitats have a lower thermal sensitivity than populations from cooler habitats.…”
Section: Discussionmentioning
confidence: 58%
“…This hypothesis could explain the overall body size reduction observed within ectotherm populations from various ecosystems (Daufresne et al 2009, Gardner et al 2011, Forster et al 2012. Such a selection would drive populations to have even higher energy requirements than predicted by the MTE as the per unit of mass energy requirement decreases with body mass (Moffett et al 2018). However, adaptive processes associated with selection on metabolic thermal traits could be expected to balance this energetic disequilibrium.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…However, in nature, warmer-source populations were not able to sustain this high reproduction to later ages and larger sizes, probably Although our data suggest that altered fecundity selection may contribute to the evolution of earlier and greater reproduction at a smaller size, our past work on mosquitofish populations in these geothermal springs also indicates that other forms of natural selection may be altered at warmer temperatures. In the wild, average female body sizes are smaller at warmer temperatures [50]. Female mosquitofish grow continuously throughout life, and their growth rates generally increase with temperature [51,52].…”
Section: Discussionmentioning
confidence: 99%
“…if the model represents ecological timescales). On these timescales, we assume that adaptive responses are negligible (but see Sandblom et al ., 2016; Moffett et al ., 2018). We investigate overall fitness with respect to temperature by calculating, the lifetime reproductive output, for a given MRN and trait parameters—we thus do not consider evolutionary consequences of changes in fitness here.…”
Section: Methodsmentioning
confidence: 99%